EDUCATIONAL DEVELOPMENT IN THE DIGITAL AGE: TRENDS AND BEST PRACTICES - Nurin Fitriana (ONTOLOGI : JURNAL PEMBELAJARAN DAN ILMIAH PENDIDIKAN, 2025)
The rapid advancement of digital technologies has significantly transformed the global education landscape. This study explores key trends and best practices in educational development within the digital age, focusing on how technology reshapes teaching, learning, and institutional strategies. Using a qualitative descriptive method based on literature review and case analysis, the study identifies several pivotal developments: increased access to education through digital platforms, the emergence of personalized and adaptive learning models, the transformation of the teacher’s role, and the implementation of blended learning approaches. The findings highlight the importance of inclusive digital policies, teacher training in digital pedagogy, and equitable access to infrastructure as core components of effective educational transformation. Despite the benefits, challenges such as the digital divide and ethical concerns in technology use remain. This research concludes that sustainable and equitable educational development in the digital age requires a holistic approach that aligns technological innovation with pedagogical goals and social equity.